TOKSIKOLOGI INSEKTISIDA RUMAH TANGGA DAN PENCEGAHAN KERACUNAN - Raini, Mariana (Media Penelitian dan Pengembangan Kesehatan, 2009)
The use of household insecticide in continuous use in a closed room, allowing its accumulation. Occurrence of this accumulation depends on several factors such as pesticide formulation, route/entrance exposure to pesticides, the attitude/behavior of pesticide users. In general insecticide enters the body through inhalation and dermal absorption. This article describes the information of household insecticide, toxicology, symptoms and signs ofpoisoning, the treatment of poisoning and the use of safe insecticide.   Key words : Insecticide, Carbamat, Pyrethroid, Repellent, Fumigant